Obtaining nickel-containing pigments from liquid waste galvanic production - Zalyhina, Volha S.; Cheprasova, Victoria I. (Journal of the Belarusian State University. Ecology, 2021)
Spent electrolytes from galvanic production are characterized by a high content of heavy metal ions, which significantly exceeds their content in natural ores. The paper shows the possibility of processing spent sulfate electrolytes from nickel plating of galvanic production to obtain pigments, which will stabilize the operation of treatment facilities, prevent the ingress of heavy metal ions into the environment, which have toxic, mutagenic and carcinogenic effects, reduce the volume of wastewater sludge formed, and also obtain a valuable commodity product that is currently being purchased abroad. The results of investigations of the coloristic characteristics of the obtained samples of pigments are presented, the effect of Fe (III) ions present in the spent electrolytes of nickel plating as a contaminant on the color characteristics and purity of the color of the obtained samples is investigated. The dependence of the color of the obtained samples on the content of Fe (III) ions in the spent electrolytes was established, which made it possible to establish the range of coloristic characteristics of pigments obtained from spent sulfate nickel-plating electrolytes (green, yellow, brown and black colors). The results of the research carried out will reduce the impact of galvanic production on the environment.
Keywords: waste; waste electrolyte; nickel plating; pigment; color; brightness; color purity; impurities